Caesarean sections in the in the context of the Chiranjeevi Yojana public private partnership program to promote institutional birth in Gujarat, India; does the embedded disincentive for caesarean section work? - Mariano Salazar; Kranti Vora; Kristi Sidney Annerstedt; Ayesha De Costa (BMC, 2019)
Abstract Background The government of Gujarat, India runs a large public private partnership program to widen access to emergency obstetric care (EmOC). The program include a disincentive for Cesareans section (CS) which are capped at seven per 100 women. In this paper, we study if the disincentive works by comparing CS rates among similar groups of women who deliver within and outside the program. Methods Community-based panel study in three districts of Gujarat, India. Sample size: 2123 women. Data was analyzed using multivariable logistic regression. Results Overall seven point seven % (164/2123) of the all women in the study had a CS. After adjusting for confounding factors women within the program had 62% (AOR 0.38, 95% CI 0.22-0.44) lower odds of having a CS than to non-beneficiaries. In a separate model of predictors of CS among women giving birth only in program accredited hospitals, we found that CY program beneficiaries had lower odds of having a CS birth than non-beneficiary women (paying clients) (AOR 0.40, 95% CI 0.24-0.67). Conclusions The Gujarat government is trying to ensure access to EmOC (including CS) for its vulnerable population through CY. The embedded disincentive to prevent unnecessary cesareans by private obstetricians is a novel one, and appears to work, though one could argue it works 'over-efficiently' by depriving some women who need CS from receiving one under the program. The state needs to revisit and review what is happening in the program periodically, and have oversight over whether women who need CS under the program actually receive the care that they need.